2007
DOI: 10.1007/s11065-007-9048-4
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Deficits in Childhood Epilepsy Syndromes

Abstract: Seizure disorders are relatively common in childhood, and the International League Against Epilepsy (ILAE) provides a hierarchical classification system to define seizure types. At the final level of classification, specific epilepsy syndromes are defined that represent a complex of signs and symptoms unique to an epilepsy condition. The present review discusses the issues related to several of these epilepsy syndromes in childhood, including those classified as generalized idiopathic epilepsies (e.g., childho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(54 citation statements)
references
References 157 publications
(195 reference statements)
0
51
0
3
Order By: Relevance
“…These functions undergo rapid developmental changes between infancy and youth and are important prerequisites for learning. Thus, global as well as specific cognitive deficits may critically affect the quality of life of children since these areas are of highest relevance for school performance [4,[6][7][8][9][10][11]. It remains unclear whether problems in patients with epilepsy are caused by the underlying etiology, by seizure semiology and/or frequency, by interictal activity in the electroencephalogram (EEG), or by negative side effects of antiepileptic drug (AED) treatment, and a multifactor explanation seems likely.…”
Section: Introductionmentioning
confidence: 99%
“…These functions undergo rapid developmental changes between infancy and youth and are important prerequisites for learning. Thus, global as well as specific cognitive deficits may critically affect the quality of life of children since these areas are of highest relevance for school performance [4,[6][7][8][9][10][11]. It remains unclear whether problems in patients with epilepsy are caused by the underlying etiology, by seizure semiology and/or frequency, by interictal activity in the electroencephalogram (EEG), or by negative side effects of antiepileptic drug (AED) treatment, and a multifactor explanation seems likely.…”
Section: Introductionmentioning
confidence: 99%
“…In LKS, structural brain abnormality is uncommon. Both computed tomography and MRI are usually normal (13,(18)(19)(20)(21)(22).…”
Section: Seizures and Screening In Lksmentioning
confidence: 99%
“…There are also reports of bizarre behavior (Kyllerman et al, 1996;Morikawa et al, 1995), emotional lability, anxiety and phobia (Morikawa et al, 1995), and of autistic-like behavior (Bulteau et al, 1995;Kyllerman et al, 1996), although a case of CSWS with autistic regression is a rare occurrence: McVicar et al (2005) conducted a retrospective review of children with language regression studied at their Institute for more than 12 years, finding that only 10 children had ESES, only one of whom had a history of autism and language regression. Some works report a deterioration of language with a tendency toward expressive aphasia with lexical and syntactic difficulties, and a generally preserved comprehension (Debiais et al, 2007;MacAllister & Schaffer, 2007), learning difficulties at school, poor reasoning and short-term memory deficits (De Negri et al, 1997;Tassinari et al, 1992;, and also motor impairments, such as ataxia, dystonia and dyspraxia (Maquet et al, 1995;Tassinari et al, 2000). Roulet-Perez et al (1993) reported clinical manifestations suggestive of a poor functioning in skills correlated to executive functions.…”
Section: Neuropsychological and Behavioral Profilementioning
confidence: 99%